“Zamach na rozum” – rzetelne dziennikarstwo czy nieodpowiedzialna pogoń za sensacją? - Wrońska, Marta; Wronska, Marta; Вронска, Марта (Видавництво Львівської політехніки, 2017)
“Замах на розум” – якісна журналістика чи безвідповідальна гонитва за сенсацією Сучасні мас-медіа є важливим джерелом інформації, засобом формування різноманітних поглядів, інтересів, а також створюють нову реальність, що зменшує довіру до ЗМІ, перетворює їх на засоби підглядання, викриття, гонитви за сенсацією, нівелюючи місію журналістики, яка має сприяти вдосконаленню суспільства

Mass media have revolutionized the contemporary man’s life. They have become an important source of information, a tool used for shaping different attitudes and interests. Their significance is especially prominent in rapidly growing digital social communication. Mass communication requires to be familiar with “the art of informing” that is to know what to convet and how to spread the news so as to achieve the best possible level of influencing the public. There are several rules and techniques which may ne used to trigger a proper audience reaction and journalists and other publicists know exactly what they are. Journalism is a social trust profession and it is based on reliability. It is hard to define what journalism ethics is. I write in my article about it. At present, not only do the media describe but also rthey create reality. Very often they cease to be mass means of communication and are becoming mass means of peeping and revealing. Unfortunatelu, social trust in media is growing less. The audience fed with information on thefts, treason, swindles is becoming not only more and more suspicious but simply tired. Mass media are becoming production companies that act on the basis of demand and supply rule. Informatiom has become a media product which is supposed to be sold for good money. In the era of huge civilization development, which we witness, mass media compete in the chase for hype, in attempt to reach the widest audience and to cater for their tastes. Abundance of medi has led to fierce competition in fighting for greater audience which, in consequence, results in lowering the quality of programmes. In 2004–2005 I conducted a series of research showing the way the media created the information on Polish education. The results clearly proved that education was not among the most important subjects and was not an area that provided input for important news. At present, journalism is not only a profession but also a mission targeted on the well-being of the society. Journalists who abandon journalism ethics are abandoning journalism itself. I decided to deal with these important aspects in my article.

Современные масс-медиа являются важным источником информации, средством формирования разнообразных взглядов, интересов, а также создают новую реальность, уменьшают доверие к СМИ, превращая их в средства подглядывания, разоблачения, погони за сенсацией, нивелируя миссию журналистики, которая должна способствовать совершенствованию общества.
“Покушение на разум” – качественная журналистика или безответственная погоня за сенсацией
“Zamach na rozum” – reliable journal or relevant pogon for sensation?
Keywords: ЗМІ; журналістиська етика; сенсація; абсурд у ЗМІ; дослідження; Mass media; journalism ethics; hype and absurdity in media; research; СМИ; журналистская этика; сенсация; абсурд в СМИ; исследования; 070; 654.1]; 159.955-021.431